2000
DOI: 10.1007/pl00008130
|View full text |Cite
|
Sign up to set email alerts
|

Transgene expression driven by heterologous ribulose-1,5-bisphosphate carboxylase/oxygenase small-subunit gene promoters in the vegetative tissues of apple (Malus pumila Mill.)

Abstract: It is desirable that the expression of transgenes in genetically modified crops is restricted to the tissues requiring the encoded activity. To this end, we have studied the ability of the heterologous ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) small-subunit (SSU) gene promoters, RBCS3CP (0.8 kbp) from tomato (hycopersion esculentum Mill.) and SRS1P (1.5 kbp) from soybean (Glycine max [h.] Mers.), to drive expression of the beta-glucuronidase (gusA) marker gene in apple (Malus pumila Mill.). Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 37 publications
(40 reference statements)
4
37
0
2
Order By: Relevance
“…Plants transformed with a constitutive 35SGUS construct stained strongly in all tissues examined except for the filament and anther wall that were only weakly stained (not shown), while non-transformed control plants showed no staining in any tissue examined (e.g., Figure 3B and 3C). These results are consistent with the data from Arabidopsis (Gittins, et al 2000;Kirby and Kavanagh 2002) and previous studies in cotton (Song et al 2000) that show that expression of the RbcS promoter is restricted primarily to photosynthetic tissues and especially in leaves. Northern blot analysis of GUS transcripts in different tissues ( Figure 4A) confirmed this result.…”
Section: Expression Of the Rbcs Promoter In Cottonsupporting
confidence: 93%
“…Plants transformed with a constitutive 35SGUS construct stained strongly in all tissues examined except for the filament and anther wall that were only weakly stained (not shown), while non-transformed control plants showed no staining in any tissue examined (e.g., Figure 3B and 3C). These results are consistent with the data from Arabidopsis (Gittins, et al 2000;Kirby and Kavanagh 2002) and previous studies in cotton (Song et al 2000) that show that expression of the RbcS promoter is restricted primarily to photosynthetic tissues and especially in leaves. Northern blot analysis of GUS transcripts in different tissues ( Figure 4A) confirmed this result.…”
Section: Expression Of the Rbcs Promoter In Cottonsupporting
confidence: 93%
“…The RbcS family is a photosynthesis-associated nuclear gene which is known to be highly expressed in green photosynthetic tissues and was therefore a suitable candidate to isolate regulatory sequences from. Gittins et al (2000) tested RbcS promoters of tomato and soybean in apple and concluded that they would be suitable for expression in green photosynthetic tissues. They found that RbcS promoters of the different origins were able to drive gus expression to half that of plants containing the CaMV35S promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter of the gene coding for the small subunit of the ribulose biphosphate carboxylase (RBC) has been studied extensively (Khoudi et al 1997;Nomura et al 2000;Gittins et al 2000;Outchkourov et al 2003) in both homologous and heterologous crops and was found to be able to provide strong transcriptional activity. RBC is one of the most abundant proteins in the plant kingdom and can constitute 40-60% of total leaf protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gittins et al (2000) studied the ability of the Rubisco promoter in apple and got 12 transgenic lines with GUS activities ranging from 1,000-35,000 pmol MU min -1 mg -1 protein. Chitinase activity of 17 transgenic alfalfa plants containing the Rubisco promoter-ech42 construct varied from 0 to 2,000 pmol MU min -1 mg -1 protein (Samac et al, 2004).…”
Section: Discussionmentioning
confidence: 99%